2022
DOI: 10.1002/ajhb.23837
|View full text |Cite
|
Sign up to set email alerts
|

Differences in wasting assessment through Middle‐Upper Arm Circumference (MUAC) adjusted by sex, age and geographic origin for children aged 6–59 months: New reference based on anthropometric surveys from 22 low‐and‐middle‐income countries

Abstract: Objectives The Middle Upper Arm Circumference (MUAC) bracelet is a widely used instrument in public health assessments and humanitarian assistance projects. The WHO guidelines present a universal cut‐off point of 115 mm to determine whether a child has severe acute malnutrition. The objective of this study is to analyze the existing differences in the MUAC for boys and girls aged between 6 and 59 months, from 22 countries distributed in three different continents, in contrast to the use of this single cut‐off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The population differences were practically nil and therefore these values could be applied universally (WHO, 2006b). Subsequent studies, in which the authors of the present study participated and which have been published in this same journal (Lescure et al, 2023;Martín-Turrero et al, 2022) have shown that growth patterns of healthy children may vary among populations of different origins, so that the WHO standards may moderately overestimate or underestimate the rates of child malnutrition in some populations.…”
Section: Composite Indexes Of Anthropometric Failure (Ciaf and Eciaf)mentioning
confidence: 73%
“…The population differences were practically nil and therefore these values could be applied universally (WHO, 2006b). Subsequent studies, in which the authors of the present study participated and which have been published in this same journal (Lescure et al, 2023;Martín-Turrero et al, 2022) have shown that growth patterns of healthy children may vary among populations of different origins, so that the WHO standards may moderately overestimate or underestimate the rates of child malnutrition in some populations.…”
Section: Composite Indexes Of Anthropometric Failure (Ciaf and Eciaf)mentioning
confidence: 73%
“…The WHO 2007 growth standards for children between the ages of 6 and 60 months were widely recognised as useful tools for nutritional assessment when it pertains to assistance from humanitarian organisations. However, certain systematic reviews [9][10][11][12][13][14] and a further study 9 identified significant variations between national or regional references that were generated while using the same inclusion criteria as well as the WHO S3).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that if paediatricians and researchers use the WHO 2007 standards to estimate the nutritional status of Pakistani children, they may incorrectly diagnose the health status of Pakistani children. The WHO 2007 standards might lack precision for South Asian countries like Pakistan, attributable to genetic and environmental distinctions between these countries and the WHO reference standards 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations